Identidade, saberes e questionamentos do professor-colaborador na realização do estágio supervisionado em educação física - Corrêa Júnior, José Firmino [UNESP] (2014)
This research is about the job of the school collaborative teacher who agrees to receive physical education students enrolled in the supervised internship process in an educational context. The challenge of the study is to uncover knowledge and the process of identity formation of collaborative teachers. Therefore, the goal here is to map the knowledge and the identity process that underlie the guidance and supervision in the physical education field. Although this cooperative teacher is legally recognized, their training and roles are still a challenge in terms of work in the Brazilian reality, thus constituting the focus of this study. Therefore, this research deals with the following question: What elements shape the cooperative teacher's knowledge and identity when monitoring the practicum teacher training? In this context, the main objective here is to understand the elements that constitute this cooperative teacher's knowledge and identity, as well as the aspects that build the cooperative process between the University and the School. Precisely, the purpose of this this paper is to: (a) analyze useful elements to describe the cooperative teacher's knowledge and identity and, (b) identify the formation of the cooperative teacher's professional profile when monitoring Physical Education interns in Basic Education Schools;. The methodological procedure chosen was qualitative research and descriptive study, since it aims at describing the characteristics of a given phenomenon. This methodology incorporates the interpretation of human cultural aspects, for its multiplicity and scope of hermeneutic approaches as a way of capturing different means of communication, using the following techniques: questionnaires, systematic observation, semi-structured interviews and content analysis. The results... (Complete abstract eletronic acess below)